Coastal saltpans are a good alternative breeding habitat for Kentish plover Charadrius alexandrinus when umbrella species are present. (17th June 2016) - Rocha, Afonso D.; Fonseca, Daniela; Masero, José A.; Ramos, Jaime A.
Abstract : The loss and degradation of natural habitats in coastal areas worldwide has adversely affected many waterbird species, changing their breeding distribution and reducing their productivity. Anthropogenic habitats such as saltpans can provide alternative or complementary habitats for waterbirds and mitigate the increasing human impact on natural coastal habitats. Unvegetated linear paths between salt ponds are used by ground‐nesting waterbird species to breed but their linear structure may facilitate the detection of nests by predators. This negative effect may, however, be counterbalanced by the advantages of breeding in mixed colonies. To evaluate the importance and the risks of breeding in saltpans we used the Kentish plover Charadrius alexandrinus breeding in coastal saltpans of southern Portugal as a model species. Specifically, we assessed the role of nest‐site characteristics, predation and nesting proximity to species with aggressive antipredator behaviour (black‐winged stilt Himantopus himantopus ) on their breeding success. Kentish plovers selected nest‐sites on the edges of paths, with about 20% of water around the nest, and a mean visibility of more than 72%; however nest‐site characteristics were not correlated with nesting success. Predation was the main cause of nest loss in saltpans (42%); carrion crows Corvus corone were responsible for most daylight nest predation (58%) and red fox ( Vulpes vulpes ; 73%) for night predation. An 8‐yr monitoring plan of a Kentish plover population showed a linear increase in their breeding success as their breeding season increasingly overlapped with that of the black‐winged stilt. An experiment with artificial nests showed a significant increase in the number of exposure days (7 to 12) when these nests were within close distance of black‐winged stilt nests. Overall, our results showed that saltpans are an important alternative breeding habitat for the Kentish plover, especially for the maintenance of mixed species colonies.